2022
DOI: 10.7554/elife.78765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of side-effect risk framing strategies on COVID-19 vaccine intentions: a randomized controlled trial

Abstract: Background:Fear over side-effects is one of the main drivers of COVID-19 vaccine hesitancy. A large literature in the behavioral and communication sciences finds that how risks are framed and presented to individuals affects their judgments of its severity. However, it remains unknown whether such framing changes can affect COVID-19 vaccine behavior and be deployed as policy solutions to reduce hesitancy.Methods:We conducted a pre-registered randomized controlled trial among 8998 participants in the United Sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Earlier research highlights the impact of both factors on vaccine hesitancy. For example, prior studies have found that, rather than actual vaccine side effects, fear of side effects is one of the main reasons for which individuals refuse to be vaccinated ( 32 ). In a randomized control trial study, Sudharsanan et al found that although COVID-19 vaccine serious side effects are rare, the media's presentation of these risks may amplify concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research highlights the impact of both factors on vaccine hesitancy. For example, prior studies have found that, rather than actual vaccine side effects, fear of side effects is one of the main reasons for which individuals refuse to be vaccinated ( 32 ). In a randomized control trial study, Sudharsanan et al found that although COVID-19 vaccine serious side effects are rare, the media's presentation of these risks may amplify concerns.…”
Section: Discussionmentioning
confidence: 99%
“…People with less education have a lower acceptance rate ( 37 ). Lower parental educational level is also a predictor of refusal of COVID-19 vaccine uptake among children ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the number of infected individuals did not substantially decrease over time, despite a gradual increase in the number of vaccinated people, we expected a decline in the vaccine’s perceived efficacy over time while anticipating an increase in safety perception. Additionally, drawing upon the principles of prospect theory [ 41 ], wherein the fear of facing adverse side effects may be a more compelling motivation than the achievement of global immunity, we hypothesized that messages highlighting the absence of risks would result in a greater willingness to receive the fourth dose compared to messages emphasizing vaccination benefits [ 69 ]. As vaccine effectiveness perception declined, we also expected a decrease in COVID-19-related concerns but an increase in perceived social pressure.…”
Section: Understanding Willingness To Vaccinate In the Covid-19 Pande...mentioning
confidence: 99%
“…Information framing has been suggested as such an intervention, including by peak international bodies such as the World Health Organization (WHO) [6] . Several studies have investigated the effect of message framing on COVID-19 vaccine intention, with varied results [7] , [8] , [9] , [10] , [11] , [12] . However, with the exception of our own research [13] , none have focused on attribute framing [14] of side effect information for actual COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%